4(x-a)+b=5x+a

Simple and best practice solution for 4(x-a)+b=5x+a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-a)+b=5x+a equation:


Simplifying
4(x + -1a) + b = 5x + a

Reorder the terms:
4(-1a + x) + b = 5x + a
(-1a * 4 + x * 4) + b = 5x + a
(-4a + 4x) + b = 5x + a

Reorder the terms:
-4a + b + 4x = 5x + a

Reorder the terms:
-4a + b + 4x = a + 5x

Solving
-4a + b + 4x = a + 5x

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
-4a + b + -1a + 4x = a + -1a + 5x

Reorder the terms:
-4a + -1a + b + 4x = a + -1a + 5x

Combine like terms: -4a + -1a = -5a
-5a + b + 4x = a + -1a + 5x

Combine like terms: a + -1a = 0
-5a + b + 4x = 0 + 5x
-5a + b + 4x = 5x

Add '-1b' to each side of the equation.
-5a + b + -1b + 4x = -1b + 5x

Combine like terms: b + -1b = 0
-5a + 0 + 4x = -1b + 5x
-5a + 4x = -1b + 5x

Add '-4x' to each side of the equation.
-5a + 4x + -4x = -1b + 5x + -4x

Combine like terms: 4x + -4x = 0
-5a + 0 = -1b + 5x + -4x
-5a = -1b + 5x + -4x

Combine like terms: 5x + -4x = 1x
-5a = -1b + 1x

Divide each side by '-5'.
a = 0.2b + -0.2x

Simplifying
a = 0.2b + -0.2x

See similar equations:

| 2(x-1)-3(2x-3)=4(-5x+7)+x | | 3x-6=5x-18 | | 2x-18x=0 | | 5(x-3)=4(2x+7) | | 3x-8=x-9 | | 6+(-7)= | | L(L-2)=168 | | 143-6x=30x+15 | | 2c+4+3c= | | (3)k=18 | | 4z(z+15)=-144 | | 2x+31=12x-59 | | 2+6y=32 | | (3y+5)(y^2-3y+4)=0 | | -9.3+r=5.1 | | 4x-2=40x+25 | | -8x+1=23 | | -10-4x=2 | | 4x+12=7(x+3) | | 8x-5=2y | | 10x-7=2y | | 3u^2+10u=-3 | | 3u^2+10u=-3 | | -(1/2)x+5=-3 | | 21x^3-14x+48=0 | | (5246246-2667247x)=8345347 | | 21x^4-14x^2+48x=0 | | 96=(2x-4)8 | | -3x(x+5)=0 | | 2(x+4)=4(x+6) | | 3(4x+5)=2(3x+5) | | (8x+5)+(-9x+5)= |

Equations solver categories